Relations between main QED and background processes at interaction of the photons with the target of the photon polarimeter - Burdeinyi, D.D.; Ganenko, V.B.; Peresun’ko, Y.P.; Shapoval, I.M.; Vashchenko, G.A. (Вопросы атомной науки и техники, 2007)
The simulation of the processes which take place at the photon interaction with matter of the polarimeter target has been carried. The relations between main QED and background processes were studied. It was found that d-electron production is the basic background process for polarimeter based on the triplet photoproduction reaction. Their total contribution is no less ~ 20 - 30% even for optimal polarimeter target (plastic with 0.1 - 0.3mm thickness). Проведено моделювання процесів, які мають місце при взаємодії фотонів із матеріалом мішені поляриметра. Вивчалися співвідношення між основними КЕД та фоновими процесами. Було знайдено, що народження d-електронів є основним фоновим процесом для поляриметра, заснованого на реакції фотонародження триплетів. Їх загальний внесок не менш ніж ~ 20 - 30% навіть для оптимальної мішені поляриметра (пластик з товщиною 0.1 - 0.3 мм). Проведено моделирование процессов, которые имеют место при взаимодействии фотонов с материалом мишени поляриметра. Изучались отношения между основными КЭД и фоновыми процессами. Было найдено, что рождение d-электронов является основным фоновым процессом для поляриметра, основанного на реакции фоторождения триплетов. Их общий вклад не менее ~ 20 - 30% даже для оптимальной мишени поляриметра (пластик с толщиной 0.1 - 0.3 мм).